![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
a. ĐKXĐ:
\(\hept{\begin{cases}\sqrt{x}-1\ne0\\x-\sqrt{x}\ne0\\x\ge0\end{cases}\Leftrightarrow\hept{\begin{cases}x>0\\x\ne1\end{cases}}}\)
b. ta có \(A=\frac{\sqrt{x}}{\sqrt{x}-1}-\frac{1}{\sqrt{x}\left(\sqrt{x}-1\right)}=\frac{x-1}{\sqrt{x}.\left(\sqrt{x}-1\right)}=\frac{\sqrt{x}+1}{\sqrt{x}}\)
c. khi \(x=\frac{1}{4}\Rightarrow\sqrt{x}=\frac{1}{2}\Rightarrow A=\frac{\frac{1}{2}+1}{\frac{1}{2}}=3\)
khi \(x=3+2\sqrt{2}\Rightarrow\sqrt{x}=\sqrt{2}+1\Rightarrow A=\frac{\sqrt{2}+1+1}{\sqrt{2}+1}=\sqrt{2}\)
\(a,ĐKXĐ:A=x\ge0;x\ne1\)
\(b,A=\frac{\sqrt{x}}{\sqrt{x}-1}-\frac{1}{x-\sqrt{x}}\)
\(A=\frac{\sqrt{x}}{\sqrt{x}-1}-\frac{1}{\sqrt{x}\left(\sqrt{x}-1\right)}\)
\(A=\frac{x-1}{\sqrt{x}\left(\sqrt{x}-1\right)}\)
\(A=\frac{\left(\sqrt{x}-1\right)\left(\sqrt{x}+1\right)}{\sqrt{x}\left(\sqrt{x}-1\right)}\)
\(A=\frac{\sqrt{x}+1}{\sqrt{x}}< =>ĐPCM\)
c,thay \(x=\frac{1}{4}\)vào A
\(c,A=\frac{\sqrt{\frac{1}{4}}+1}{\sqrt{\frac{1}{4}}}\)
\(A=\frac{\frac{1}{2}+1}{\frac{1}{2}}\)
\(A=3\)
\(x=3+2\sqrt{2}\)
\(x=\sqrt{2}^2+2\sqrt{2}+1\)
\(x=\left(\sqrt{2}+1\right)^2\)thay x vào A
\(A=\frac{\sqrt{\left(\sqrt{2}+1\right)^2}+1}{\sqrt{\left(\sqrt{2}+1\right)^2}}\)
\(A=\frac{\sqrt{2}+1+1}{\sqrt{2}+1}\)
\(A=\frac{2+\sqrt{2}}{\sqrt{2}+1}\)
\(A=\frac{\sqrt{2}\left(\sqrt{2}+1\right)}{\sqrt{2}+1}=\sqrt{2}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
1.\(x=7+4\sqrt{3}\)
\(=\left(\sqrt{3}+2\right)^2\)
Thay x=\(\left(2+\sqrt{3}\right)^2\), ta có:
\(A=\frac{3+\sqrt{3}}{4+\sqrt{3}}\)
2. \(B=\frac{\sqrt{x}\left(\sqrt{x}-2\right)-\left(\sqrt{x}-1\right)\left(\sqrt{x}+1\right)-\sqrt{x}-4}{\left(\sqrt{x}+1\right)\left(\sqrt{x}-2\right)}\)
\(B=\frac{-3}{2-\sqrt{x}}\left(đpcm\right)\)
3. \(\frac{B}{A}=\frac{\frac{-3}{2-\sqrt{x}}}{\frac{\sqrt{x}+1}{\sqrt{x}+2}}=\frac{-3}{2-\sqrt{x}}.\frac{\sqrt{x}+2}{\sqrt{x}+1}\)
\(\frac{B}{A}< -1\Rightarrow\frac{3\left(\sqrt{x}+2\right)}{\left(\sqrt{x}-2\right)\left(\sqrt{x}+1\right)}< -1\)
\(\Leftrightarrow\frac{3\sqrt{x}+6+x-\sqrt{x}-2}{\left(\sqrt{x}-2\right)\left(\sqrt{x}+1\right)}< 0\)
\(\Leftrightarrow\frac{x-2\sqrt{x}+4}{x-\sqrt{x}-2}< 0\)
\(\Rightarrow x-\sqrt{x}-2< 0\)(Vì \(x-2\sqrt{x}+4>0\))
\(\Leftrightarrow-1< x< 2\)
\(A=\frac{\sqrt{x}+1}{\sqrt{x}-1}=\frac{\sqrt{4+2\sqrt{3}}+1}{\sqrt{4+2\sqrt{3}}-1}\)\(=\frac{\sqrt{\left(\sqrt{3}\right)^2+2\cdot\sqrt{3}\cdot1+1^2}+1}{\sqrt{\left(\sqrt{3}\right)^2+2\cdot\sqrt{3}\cdot1+1^2}-1}\)
\(=\frac{\sqrt{\left(\sqrt{3}+1\right)^2}+1}{\sqrt{\left(\sqrt{3}+1\right)^2}-1}=\frac{\sqrt{3}+1+1}{\sqrt{3}+1-1}=\frac{\sqrt{3}+2}{\sqrt{3}}=\frac{\left(\sqrt{3}+2\right)\sqrt{3}}{\sqrt{3}\cdot\sqrt{3}}\)\(=\frac{3+2\sqrt{3}}{3}\)
ket ban voi mk nha